Extraction and analysis of long chain fatty acids adsorbed onto active and inactivated anaerobic sludge - Pires, O. C. (2001)
Extraction and GC analysis of the adsorbed long chain fatty acids onto active and inactivated sludge taken from two EGSB reactors fed with oleic acid as the sole carbon source at 6 kgCOD/m3.day was determined. No gradual acclimation of sludge to this LCFA was performed. Active sludge had been overloaded with oleic acid in a previous experiment and a possible retrieval of its activity was investigated. However the results revealed that the average removal efficiency was as low as 35% and only 19% of the biogas was methane. In the inactive reactor COD removal efficiency was 14%, corresponding only to physical adsorption, because no methane was produced. Extraction and analysis of the adsorbed fatty acids revealed that in the active sludge palmitic acid was the dominant fatty acid, in average, 3 to 52 times higher than oleic acid. In the inactivated sludge the main fatty acid detected was oleic acid, 8 times higher than palmitic acid.